Streptomyces Dominate the Soil Under Betula Trees That Have Naturally Colonized a Red Gypsum Landfill - Zappelini, Cyril; Alvarez-Lopez, Vanessa; Capelli, Nicolas; Guyeux, Christophe; Chalot, Michel (Frontiers in Microbiology, 2018)
The successful restoration of well-engineered tailings storage facilities is needed to avoid mine tailings problems. This study characterized the bacterial communities from vegetated and non-vegetated soils from a red gypsum landfill resulting from the industrial extraction of titanium. A set of 275 bacteria was isolated from vegetated soil and non-vegetated soil areas and taxonomically characterized using BOX-PCR. The study also evaluated the ability of a subset of 88 isolated bacteria on their ability to produce plant growth promoting (PGP) traits [indoleacetic acid (IAA) production, phosphate solubilization, and siderophore production] and their tolerance to potentially toxic elements (PTEs). Twenty strains were chosen for further analysis to produce inoculum for birch-challenging experiments. Principal component analysis (PCA) showed that the set of pedological parameters (pH, granulometry, carbon, organic matter, and Mg content) alone explained approximately 40% of the differences between the two soils. The highest density of total culturable bacteria was found in the vegetated soil, and it was much higher than that in the non-vegetated soil. The Actinobacteria phyla dominated the culturable soil community (70% in vegetated soil and 95% in non-vegetated soil), while the phyla Firmicutes (including the genus Bacillus) and Bacteroides (including the genera Pedobacter and Olivibacter) were found only in the vegetated soil fraction. Additional genera (Rhizobium, Variovorax, and Ensifer) were found solely in the vegetated soil. The vegetated soil bacteria harbored the most beneficial PGP bacteria with 12% of the isolates showing three or more PGP traits. The strains with higher metal tolerances in our study were Phyllobacterium sp. WR140 (RO1.15), Phyllobacterium sp. WR140 (R01.34), and Streptomyces sp. (R04.15), all isolated from the vegetated soil. Among the isolates tested in challenging experiments, Phyllobacterium (R01.34) and Streptomyces sp. (R05.33) have the greatest potential to act as PGP rhizobacteria and therefore to be used in the biological restoration of tailings dumps.